Il sacrificio dell'orso - Scarduelli, Pietro (L'Uomo società tradizione sviluppo, 2019)
The author considers various aspects of the system of myths and ritual of Siberian peoples centered on the figure of the bear and, in particular, on the rituals involved in the extensive practice of bear hunting as well as in the «bear feast». The author also examines myths concerning the heavenly origin of the bear and its function as «cultural hero». What emerges is that the myths and ritual reveal a logical framework that conceptualizes relations of domination and subordination within the group, and the bear functions as a mediator between men and heavenly beings. Thus it is possible to establish a social hierarchy based on the special ceremonial relations that some groups enjoy with the bear.